Поглотители СВЧ-энергии с высокой теплопроводностью на основе AlN и SiC с добавками молибдена - Chasnyk, V. I.; Fesenko, I. P. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
The paper presents the results of experimental studies of thermal conductivity and microwave absorption in aluminum nitride based composites with different percentages of silicium carbide and molybdenum. It is shown that the optimal composition of the studied materials is the composite with 46% of silicium carbide and 4% of molybdenum. This composition reveals high UHF-energy absorption level of 42 dB/cm in the frequency range of 9.5—10.5 GHz and high thermal conductivity of 65 W/(m.K).